Effect of pre-forming and pressure path on deformation behavior in multi-pass hydrodynamic deep drawing process. (February 2017) - Li, W.D.; Meng, B.; Wang, C.; Wan, M.; Xu, L.
Abstract: Hydrodynamic deep drawing (HDD) is an effective method for the fabrication of the sheet metal parts with deep cavity and complex surface configuration. Despite the remarkable progress that has been made on the development of one-stroke HDD process, a number of fundamental challenges are still unsolved in the multi-stage HDD technology due to the unique process allocation and continuous deformation behavior. In this study, the effect of pre-forming parameters and loading locus of cavity pressure on the sequential deformation of aluminum alloy is explored to determine the suitable working conditions to form a conical part with deep cavity using multi-pass HDD process. Based on the equal allowance function method, the material deformation amount for the multi-pass process is allocated and optimized. In addition, the defect patterns including wrinkling and tearing during the multi-step process are discussed. The effect of pre-forming depth and loading loci of cavity pressure on the dimensional accuracy and thickness variation of the workpiece is analyzed, the appropriate pre-forming depth and loading loci of cavity pressure are achieved by using numerical models implementing diverse yield criteria. The results mirror that yld2000-2d and BBC2005 yield functions predict the pre-forming depth more accurately with respect to Von Mises isotropic formulation and Hill'48 yield criterion. However, the prediction accuracy of the pre-forming stage is superior to that of the final forming period using yld2000-2d yield formula due to the error accumulation and the effect of prestrain on the sequential process. Moreover, the reasonable loading path of cavity pressure for the intermediate cylindrical part is characterized by three feature points, whereas the suitable pressure locus for the final conical part is featured with four unique points and three distinct segments containing low-pressure stage, pressure-raising stage and full pressure period. By using the suitable working conditions, the well-formed conical part with homogenous thickness distribution, desirable surface finish, and high dimensional precision is fabricated, which highlights that the proposed multi-step HDD technology is valid for the integration and precision forming of the workpiece with complex feature and high drawing ratio. Graphical abstract: Highlights: Pre-forming depth was accurately predicted using Yld2000 and BBC2005 yield criteria. Reasonable pressure path for preformed cylindrical part owns three feature points. Optimal pressure locus for the conical part is featured by three distinct segments. Low prediction accuracy for the final forming pass results from strain cumulation.